2010
DOI: 10.1089/dia.2009.0133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Microalbuminuria Among Patients with Type 2 Diabetes Mellitus—A Hospital-Based Study from North India

Abstract: The high proportion of patients who present with albuminuria within the first year of diagnosis probably indicates longer duration of prior undiagnosed diabetes. Screening for asymptomatic diabetes and defining newer risk factors to identify those at risk for complications are essential to reduce the socioeconomic burden of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 23 publications
(34 reference statements)
6
23
2
Order By: Relevance
“…Similar results were obtained in study done by Hetal Pandya et al, Ram Vinod Mahato et al and Prashant Tayde et al 4,6,7 In our study prevalence of Diabetic Nephropathy was 41 %, micro albuminuria was present in 25 % patients and 16% had macro albuminuria. Similar results were obtained in studies done by Mohammed Ahmed Bamashmoos Krairittichai U, et al, Kanakamani J, et al [8][9][10] Out of 59 patients with normal AER, 30.5 % patients had GFR < 90 ml/min/1.73m 2 whereas rest of the patients had GFR > 90ml/min/1.73 m 2 . Study done by Macisaac RJ and Jerums G has shown that 20 % patients with type 2 diabetes have GFR <60ml/min/1.73m 2 while remaining normo albuminuric.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were obtained in study done by Hetal Pandya et al, Ram Vinod Mahato et al and Prashant Tayde et al 4,6,7 In our study prevalence of Diabetic Nephropathy was 41 %, micro albuminuria was present in 25 % patients and 16% had macro albuminuria. Similar results were obtained in studies done by Mohammed Ahmed Bamashmoos Krairittichai U, et al, Kanakamani J, et al [8][9][10] Out of 59 patients with normal AER, 30.5 % patients had GFR < 90 ml/min/1.73m 2 whereas rest of the patients had GFR > 90ml/min/1.73 m 2 . Study done by Macisaac RJ and Jerums G has shown that 20 % patients with type 2 diabetes have GFR <60ml/min/1.73m 2 while remaining normo albuminuric.…”
Section: Discussionsupporting
confidence: 87%
“…Mean age of patients with diabetes in the present study was 50.57 years, which is similar to that, reported by Chowta et al 6 , Kanakmani et al 12 and Maskari et al 13 whereas, in the studies of Tandon et al 8 the patients belonged to a younger age group with mean age of 52.2 years. Generally, diabetic nephropathy affects both males and females equally.…”
Section: Results:-supporting
confidence: 89%
“…The search for reliable urinary markers predicting DN has been ample as reflected by a recent study by Kanakamani et al, which assessed 670 patients with DM and CKD [55]. It utilized urinalysis to evaluate the predictive role of microalbuminuria in DN patients [55].…”
Section: Urinary Markersmentioning
confidence: 99%
“…It utilized urinalysis to evaluate the predictive role of microalbuminuria in DN patients [55]. It showed no statistically significant correlation between the median diabetic duration and the prevalence of microalbuminuria, as reflected by microalbuminuria prevalence being 25.5% (95% confidence interval (CI), 22.4-29%) and 24.7% in those with median diabetic duration of 5 years and DM of < 1 year, respectively [55].…”
Section: Urinary Markersmentioning
confidence: 99%